Assessing the Feasibility and Acceptability of the Daybreak Drink Tracker: Prospective Observational Study - Kathryn Fletcher; Dominique Robert-Hendren (JMIR Formative Research)
Abstract BackgroundExcessive alcohol use is associated with significant harms, with wide-ranging social and economic impacts. Efforts to prevent and reduce the harmful use of alcohol are a public health priority. Smartphone apps have the potential to provide accessible and cost-effective support to those seeking to reduce alcohol consumption; however, the evidence base regarding which components are effective is lacking. Self-monitoring is considered as one of the most effective components for behavior change across multiple health domains, yet there is mixed evidence for its role in the alcohol use space. An improved understanding of the use, acceptability, and outcomes of smartphone apps and their inherent components is required to determine their potential role in alcohol behavior change. ObjectiveWe investigated the feasibility and acceptability of the Drink Tracker, a novel feature of the commercially available Daybreak (Hello Sunday Morning) app. MethodsThe Daybreak app is accessible worldwide via major app stores and is offered free of charge to Australian residents. Individuals (aged over 18 years) registering for Daybreak were invited to access the Drink Tracker to monitor their alcohol consumption as part of an uncontrolled observational prospective study. Feasibility was assessed via uptake and frequency of use of the Drink Tracker. Acceptability was measured via participant feedback to determine overall satisfaction, perceived helpfulness, and likelihood of recommending the Drink Tracker to others. Self-reported changes in alcohol consumption (Alcohol Use Disorders Identification Test score) and psychological distress (Kessler Psychological Distress Scale score) at 3-month follow-up were also measured. Preliminary data collected for the first 4 months (October 2023 to February 2024) of the study were reported, including 3-month follow-up outcomes. ResultsFeasibility was demonstrated, with almost 70% (2847/4119) of those registering for Daybreak going on to access the Drink Tracker. Of those accessing the Drink Tracker, 71.1% (n=2024) consented to research, comprising the final participant sample. Frequency of use was high, with over half of participants (1112/2024, 54.9%) using the Drink Tracker more than once, and more than one-third (757/2024, 37.4%) using the Drink Tracker more than 5 times. Of the 30 participants completing a 3-month follow-up, acceptability was high, with 73% (n=22) reporting high satisfaction levels with the Drink Tracker overall, 87% (n=26) indicating it was easy to use and rating a mean score of 7.7 (SD 2.8) out of 10 in terms of likelihood of recommending to others. Significant reductions in alcohol consumption (PP ConclusionsOur results suggest that the Daybreak Drink Tracker is highly feasible and acceptable in supporting individuals accessing commercially available smartphone apps to change their relationship with alcohol. While positive clinical outcomes were observed, the absence of a control group disallows any conclusions with regard to the efficacy of the Drink Tracker. Further testing via a randomized controlled trial is required.